(untitled) (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2023)
The relevance of studying the digitalization of the economy of Uzbekistan is due to the slowdown in economic growth in the world, as well as the need to change some obsolete aspects of the economy. The article considers the features of the digital development of the country’s economy. Particular attention is paid to the banking sector. The article reveals the features of digital banks and analyzes the problems and trends of their development in Uzbekistan. Based on the Strategy for Reforming the Banking System of the Republic of Uzbekistan for 2020–2025. conclusions are drawn on the further development of the digital banking system in the country. The result of the study is an assessment of the importance of digital transformation for the state economy.